A framework for the use of competencies for achieving competitive advantage - Terry Meyer; Paul Semark (South African Journal of Business Management, 1996)
Competency, its nature, its acquisition and its maintenance, is emerging as the pivotal dimension of human development for employability, corporate competitive advantage and national economic success. It is, however, a concept still fogged by misunderstanding and debate. The authors of this article attempt to clear the fog by providing a succinct conceptual framework which integrates the contributions of many theorists and accommodates the use of the term in a variety of contexts. In addition, they propose that competencies are more than the essence of a national qualifications framework, or of corporate training programmes, as they are intimately linked to strategy with all its implications. Competency, therefore, is a central Issue for managers seeking competitive advantage.
Keywords: 650